The value of hsa_circ_0058514 in plasma extracellular vesicles for breast cancer - Liu, Jiani; Peng, Xinyu; Yang, Yang; Zhang, Yao; Han, Meng; Shi, Xiaohui; Zheng, Jie; Li, Tong; Chen, Jinxia; Lv, Weihua; Liu, Yunjiang; Qi, Yixin; et al. (Frontiers in Oncology, 2022)
The aim of this study was to investigate the diagnostic value of hsa_circ_0058514 in plasma extracellular vesicles (EVs) in BC patients and its predictive value for neoadjuvant chemotherapy. The expression of hsa_circ_0058514 in a large sample of BC plasma and healthy subjects’ plasma was detected by qPCR, and the ROC curve was drawn to verify its diagnostic value as a plasma tumor marker. Furthermore, the association between the expression of hsa_circ_0058514 and clinicopathological characteristics before and after treatment was detected in the plasma of 40 pairs of BC patients undergoing neoadjuvant therapy. The expression level of hsa_circ_0058514 in the plasma of BC patients was significantly higher than that of healthy subjects. The ROC curve showed that plasma hsa_circ_0058514 ROC in differentiating non-metastatic BC and healthy people had better diagnostic efficiency than conventional tumor markers CA153, CA125, and CEA. In patients with neoadjuvant therapy, the decrease in plasma hsa_circ_0058514 value before and after treatment correlated with pathological MP grade (r = 0.444, p = 0.004) and imaging tumor regression value (r = 0.43, p = 0.005) positive correlation. The detection of hsa_circ_0058514 in both extracellular vesicles of BC cell culture medium and human plasma was demonstrated. Hsa_circ_0058514 is detected in the plasma from BC cells secreted in the form of vesicles. Hsa_circ_0058514 can be used as an early plasma biological indicator for the diagnosis of BC in clinical applications, with a higher risk of recurrence and metastasis, and as a predictor of the effect of neoadjuvant therapy to guide the clinical use of neoadjuvant therapy.